The value of best-practice guidelines for OSCEs in postgraduate program in an Australian remote area setting - Jeffrey, C.; Mitchell, M.; Henderson, A.; Lenthall, S.; Knight, S.; Glover, P.; Kelly, Michelle; Nulty, D.; Groves, M. (Australian Rural Health Education Network, 2014)
Introduction: Nurses in remote areas of Australia are the primary healthcare professionals, who need to be able to deliver comprehensive and culturally sensitive care to clients, many of whom are Indigenous Australians. Adequate and specific preparation for practice is crucial to the quality of care delivered by remote area nurses (RANs). Objective structured clinical examinations (OSCE) provide an excellent opportunity for student practice in a simulated environment that is safe, authentic, fair and valid when well constructed. Seven integrated best practice guidelines (BPGs), previously developed by project team members to inform OSCEs within educational programs, provided guidance in restructuring the OSCE. This paper provides a detailed analysis of the value of BPGs used in the development, teaching and learning, and evaluation of OSCEs in a rural and remote postgraduate course for RANs. Method: A pre-site visit to the Centre for Remote Health, Alice Springs, Northern Territory, was conducted with modification of the course and previous OSCE according to BPGs. Following delivery of the course and OSCE, evaluations occurred via a mixed method approach. Student surveys (n=15) and focus groups (n=13) and staff interviews (n=5) provided an in-depth analysis of their perceptions of the revised OSCE. Descriptive statistics were used to describe the student sample. The narrative data were transcribed verbatim and analysed using content analysis. Triangulation was achieved with the convergence of the separate data sources focusing on themes and patterns within and between students and tutors.Results: All 15 students and five tutors provided feedback. The majority of student participants had limited experience in working in remote area nursing prior to participation and therefore the opportunities that availed themselves were critical in adequately equipping them with the requisite knowledge, skills and abilities. Three themes emerged from the data: (1) value of common and significant events in OSCE; (2) power of deliberate actions; and (3) learning cultural sensitivity.Discussion: OSCEs in this setting proved to be a good way for students to learn the skills required by RANs. Overwhelmingly, the modifications using the BPGs were highly valued by students and staff. Three themes emerged and were clearly linked to specific BPGs, indicating the positive impact the BPGs had on the OSCEs and student learning. The authentic content for the scenarios was seen as relevant and motivational for student learning. The practice element of the OSCEs enhanced the learning experience and feedback supported learning. Conclusions: OSCEs developed, taught and assessed using BPGs were highly valued. The BPGs provided an integrated approach with real-life scenarios with a strong cultural perspective – all important features to the RANs’ future success in providing individualised care to clients in remote areas of Australia. Further use of BPGs is recommended.